Reading the Resistance of Hegemony on Historical Activities in Indonesia - Andrian Dektisa Hagijanto; Erandaru Srisanto (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
Indonesian reenactors imitate the characteristics of the troops during the independence war. It becomes a euphoric event in commemorating the battles and history learning activity. The activity itself is perceived as the source of history learning when it is creatively crafted to be a media content and uploaded in social media. It is a kind of excavation towards the history of independence war from the alternative perspective, which has never been disclosed before. The reenactors narrate the perspective of the history of Indonesia independence war as, what is interpreted in this writing, the articulation of hegemony counter. It becomes an example of the operationalization theory of Cox and Schilthuis inspired by Antonio Gramsci. It is a kind of expression of resistance towards the State system and politics from the intellectual concept. Resistance using the history education as the subject becomes a kind of hegemony counter done by society groups which are not included in marginalized society. This paper uses the method of library research, observation and visual analysis interview using the Barthesian semiology perspective.